Management of Domestic Violence by Primary Care Physicians in Hong Kong: Association With Barriers, Attitudes, Training, and Practice Background. Issue 19 (October 2021) - Sun, Kai Sing; Lam, Tai Pong; Piterman, Leon; Lam, Kwok Fai; Tang, Wai Sin; Kwok, Kit Wing; Chan, Hoi Yan; Wu, Dan; Tiwari, Agnes
While primary care physicians (PCPs) have opportunities to recognize patients who encounter domestic violence (DV) by intimate partners, warning symptoms such as unexplained physical injury, bruising, anxiety, and depression are often missed during clinic visits. This study investigated the barriers of Hong Kong PCPs toward managing DV, including recognition, management, and referrals of these patients. Four focus group interviews were conducted to explore the in-depth opinions of PCPs on managing DV in Hong Kong. The themes identified were investigated in a questionnaire survey with data from 504 PCPs working in public and private sectors. Factor analysis of the survey data suggested four major barrier factors: (a) worries about the potential harms of intervening in patients' domestic affairs and DV issues, (b) lack of guidelines and support services, (c) limited skills and time in managing DV, and (d) patients' reluctance in disclosing DV issues. PCPs with more years of practice had more worries about intervening in domestic issues (Factor 1), while the younger PCPs tended to perceive limited skills and time in managing DV cases as barriers (Factor 3). PCPs working in the public setting were more likely to ask patients about DV ( M = 5.4 vs. 2.9), suspected DV ( M = 3.8 vs. 2.3), and managed DV ( M = 1.7 vs. 1.0) in the past 5 years compared with the private PCPs. Some PCPs in the focus groups expressed the view that DV cases should be handled by social workers instead of doctors. Survey respondents who held such views about doctors' limited role in DV management also scored higher in all of the barrier factors. The findings suggest that there are boundaries between domestic and medical realms, especially in a Chinese context. Resolving PCPs' worries by training, provision of DV management guidelines, and referral pathway to social workers may be good starting points to bridge the gaps.